2023
DOI: 10.1177/26335565221149623
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of multimorbidity among a community-based cohort in rural India

Abstract: Background Multimorbidity estimates are expected to increase in India primarily due to the population aging. However, there is a lack of research estimating the burden of multimorbidity in the Indian context using a validated tool. We estimated the prevalence and determinants of multimorbidity amongst the adult population of the rural Uddanam region, Andhra Pradesh. Methods This community-based cross-sectional study was conducted as a part of an ongoing research program. Multistage cluster sampling technique w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
(81 reference statements)
0
5
1
Order By: Relevance
“…Many studies of multimorbidity are based on medical records [2][3][4] and miss most of the burden of undiagnosed and untreated disease. Many studies are conducted in specific locations, [5][6][7] which are not nationally representative, or are conducted only in older adults. [7][8][9][10] National household surveys typically rely on self-reported measures of past diagnosis or symptoms 8 9 11 and are often underpowered to estimate the prevalence of less frequent condition combinations.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…Many studies of multimorbidity are based on medical records [2][3][4] and miss most of the burden of undiagnosed and untreated disease. Many studies are conducted in specific locations, [5][6][7] which are not nationally representative, or are conducted only in older adults. [7][8][9][10] National household surveys typically rely on self-reported measures of past diagnosis or symptoms 8 9 11 and are often underpowered to estimate the prevalence of less frequent condition combinations.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…A recent study has shown a high prevalence of multimorbidity in a chronic kidney diseases of unknown origin endemic area. 142 …”
Section: Climate Change and Its Impact On Healthmentioning
confidence: 99%
“…Current evidence on the burden of multimorbidity in rural and urbanising India is limited. Incidence data are lacking, while prevalence estimates have fluctuated widely (ranging from 9% to 59%) owing to a frequent reliance on self-reported disease, which is known to grossly underestimate true disease prevalence in these settings 6–9. There is some evidence that multimorbidity clusters in India mirror those reported in high-income countries, specifically, clustering of cardiorespiratory (angina, asthma, chronic obstructive pulmonary disease (COPD)), metabolic (diabetes, obesity, hypertension) and mental articular (arthritis and depression) conditions 10–14.…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that multimorbidity clusters in India mirror those reported in high-income countries, specifically, clustering of cardiorespiratory (angina, asthma, chronic obstructive pulmonary disease (COPD)), metabolic (diabetes, obesity, hypertension) and mental articular (arthritis and depression) conditions 10–14. However, multimorbidity clusters specific to rural and urbanising India may have not been identified as several locally prevalent conditions (eg, anaemia) were not measured in prior studies 9–11 13 14…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation